2002
DOI: 10.1021/bi026288h
|View full text |Cite
|
Sign up to set email alerts
|

Deamidation, but Not Truncation, Decreases the Urea Stability of a Lens Structural Protein, βB1-Crystallin

Abstract: Crystallins, the major structural proteins in the lens of the eye, are maintained with little turnover throughout the lifetime of the host. With time, lens crystallins undergo post-translational modifications that may play an important role in loss of vision during aging and cataract formation. Specific modifications include deamidation and truncation. Urea-induced denaturation was studied for recombinantly expressed wild-type betaB1 (WT), the deamidated mutant (Q204E), an N-terminally truncated mutant (betaB1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
79
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 72 publications
(89 citation statements)
references
References 34 publications
7
79
1
Order By: Relevance
“…These CD spectra are in agreement with the results previously reported by Lampi et al on B1 (19) and Kim et al on B1∆N41 (23). Since it is the peptide backbone that absorbs in the far-UV range, truncation of 41 amino acids is expected to affect the value of the molar ellipticity.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…These CD spectra are in agreement with the results previously reported by Lampi et al on B1 (19) and Kim et al on B1∆N41 (23). Since it is the peptide backbone that absorbs in the far-UV range, truncation of 41 amino acids is expected to affect the value of the molar ellipticity.…”
Section: Resultssupporting
confidence: 92%
“…However, circular dichroism and fluorescence studies on B1 have shown that truncation does not affect the unfolding/ refolding properties of the protein (23).…”
mentioning
confidence: 99%
“…Simulating deamidation in the C-terminal domain at Q204 in βB1 homologous to Q162 in βB2 was associated with a decrease in stability of the N-terminal domain (20).…”
Section: Effects Of Deamidation On βB2 Stabilitymentioning
confidence: 98%
“…Thus, Trp emission strongly contributed to the emission at 285 m (Figure 8). The maximum intensity for β B1 was at 336 nm and for β B2 at 227 nm, reflecting the fewer exposed Trp (35,38,47), with PB2 having only one exposed and one partially buried Trp (47).…”
Section: Effect Of Deamidation On βA3-crystallin Structurementioning
confidence: 99%
“…Thus, Trp emission strongly contributed to the emission at 285 m (Figure 8). The maximum intensity for β B1 was at 336 nm and for β B2 at 227 nm, reflecting the fewer exposed Trp (35,38,47), with PB2 having only one exposed and one partially buried Trp (47).Simulating deamidation in vitro at the predicted domain interface of βA3 did not dramatically alter secondary structure as indicated by only slight differences in the far-UV CD. There were Takata et al…”
mentioning
confidence: 97%